Investigation of auditory distance perception and preferences in concert halls by using virtual acoustics - Kuusinen, Antti; Lokki, Tapio (The Journal of the Acoustical Society of America, 2015)
Virtual acoustics with multichannel sound reproduction was used to study auditory distance perception in four concert halls with multiple sound sources on stage. Eight subjects reported apparent auditory distances in five seating positions from 10 to 26 m to the middle of the sources on stage. The distance estimates were collected by absolute distance estimation procedure as well as a free modulus estimation procedure including both within and between halls evaluations. In addition, pairwise preferences were collected for two positions within each hall and for one position between halls. Results reveal that the perception of distance is dependent on the hall acoustics and show how the strength factor G and direct-to-reverberant energy ratio covary in relation to perceptual distances in these halls. The results also indicate that in such large spaces the overestimation of short distances may continue up to and further than 10 m from the sound sources. Preference results show that closer seats were liked more than further ones and that the strength of this preference is associated with the difference in perceptual distances.